Recombinant heat shock protein 70 in combination with radiotherapy as a source of tumor antigens to improve dendritic cell immunotherapy - Wang, Yu-Shan; Liu, Shih-Jen; Huang, Su-Chen; Chang, Chao-Chun; Huang, Yi-Chun; Fong, Weng-Lam; Chi, Mau-Shin; Chi, Kwan-Hwa (Frontiers in Oncology, 2012)
Local radiotherapy (RT) plus intratumoral dendritic cell (DC) injection can mediate immunological response. We hypothesized that co-injection of exogenous recombinant heat shock protein 70 (rHsp70) in combination with RT-DC could be as effective as co-injection of HSP-peptide for evoking specific immune response. rHsp70-prostate-specific antigen (rHSP70C'-PSA) and alpha-fetoprotein (rHSP70C'-AFP) were used to compare specific response. Growth inhibition of the tumor and the systemic anti-tumor immune response were measured on CT26/PSA and CT26/AFP mice model. Intratumoral co-injection of rHsp70 and DC into the irradiated tumor site induced a more potent anti-tumor immune response than injection of DC alone. rHsp70 was as effective as rHsp70C'-PSA or rHsp70C'-AFP in inducing a tumor-specific cytotoxic T lymphocyte response or tumor growth delay. These results demonstrate that co-administration with rHsp70 and radiotherapy could be a simple and effective source of tumor antigens to achieve RT-DC immunotherapy protocol and easy to apply in clinical use.